2020
DOI: 10.1101/2020.09.16.291930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BRD4-mediated repression of p53 is a target for combination therapy in AML

Abstract: SummaryAcute Myeloid Leukemia (AML) is a typically-lethal molecularly heterogeneous disease, with few broad-spectrum therapeutic targets. Unusually, most AML retain wild-type TP53, encoding the pro-apoptotic tumor suppressor p53. MDM2 inhibitors (MDM2i), which activate wild-type p53, and BET inhibitors (BETi), targeting the BET-family co-activator BRD4, both show encouraging pre-clinical activity, but limited clinical activity as single agents. Here, we report synergistic toxicity of combined MDM2i and BETi to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…Additional combinations of targeted therapy and, more recently, with immunotherapy have been identified that can overcome resistance (Luke et al ., 2017). Similar effects have been observed for a wide variety of cancers, including AML, lung cancer and breast cancer (Fisusi and Akala, 2019; Latif et al ., 2021; Yuan et al ., 2019), and combination treatment clearly has the potential to significantly improve survival rates for cancer patients. However, given the sheer number of targeted therapies, identifying synergistic drug combinations is a major challenge, and several obstacles still need to be overcome.…”
Section: Introductionsupporting
confidence: 77%
“…Additional combinations of targeted therapy and, more recently, with immunotherapy have been identified that can overcome resistance (Luke et al ., 2017). Similar effects have been observed for a wide variety of cancers, including AML, lung cancer and breast cancer (Fisusi and Akala, 2019; Latif et al ., 2021; Yuan et al ., 2019), and combination treatment clearly has the potential to significantly improve survival rates for cancer patients. However, given the sheer number of targeted therapies, identifying synergistic drug combinations is a major challenge, and several obstacles still need to be overcome.…”
Section: Introductionsupporting
confidence: 77%
“…A majority of AML cases contain wild-type TP53, and only 8% of de novo AML cases contain TP53 mutations according to TCGA. However, p53 is often rendered functionally deficient by over-expression of MDM2 (Latif et al, 2021). Selinexor blocks nuclear export and traps both proteins in the nucleus, thus hindering the MDM2-dependent shuttling of MDM2-p53 targeted for cytoplasmic degradation and hence induces transcriptional upregulation through phosphorylation of these sites (O'Keefe et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The pathways/genes by which BRD4 affects BACE1 and APP processing in our AD model cells may associate with BRD4-related cell cycle and proliferation (CDKN1B, NRF2) or autophagy (18,51,52), which warrants future studies. Interestingly, using an oxidative stress-dependent activity, BRD4 binds and regulates the transcriptional factors p53 and SP1 (53,54), which have been related to the transcription of APP and BACE1 in AD (55,56). These results showed complex circuits for the regulatory role of BRD4 in transcriptional gene regulation.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 93%